Characterizing Tetraploid Populations of Actinidia chinensis for Kiwifruit Genetic Improvement - Zhi Wang; Guangming Hu; Zuozhou Li; Caihong Zhong; Xiaohong Yao (Plants, 2022)
Understanding genetic diversity and structure in natural populations and their suitable habitat response to environmental changes is critical for the protection and utilization of germplasm resources. We evaluated the genetic diversity and structure of 24 A. chinensis populations using simple sequence repeat (SSR) molecular markers. The potential suitable distribution of tetraploid A. chinensis estimated under the current climate and predicted for the future climate was generated with ecological niche modeling (ENM). The results indicated that the polyploid populations of A.chinensis have high levels of genetic diversity and that there are distinct eastern and western genetic clusters. The population structure of A. chinensis can be explained by an isolation-by-distance model. The results also revealed that potentially suitable areas of tetraploids will likely be gradually lost and the habitat will likely be increasingly fragmented in the future. This study provides an extensive overview of tetraploid A. chinensis across its distribution range, contributing to a better understanding of its germplasm resources. These results can also provide the scientific basis for the protection and sustainable utilization of kiwifruit wild resources.